[Boat people ; New beginnings ; Kabuki - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Discusses the Vietnamese boat people rescued by a Canadian ship who took refuge in the Philippines. Also includes interviews with Vietnamese, Drug addicts and alcoholics taken care of in a house founded by Peter to Zobel in Paranaque.
Boat people (15 min.) -- New beginnings (14 min.) -- Kabuki (16 min.).
VHS.
Keywords: Refugees, Vietnamese; Drug abuse -- Treatment -- Philippines; Narcotic addicts -- Mental health services -- Philippines; Alcoholics -- Rehabilitation; Kabuki